Identification of the Process and Characteristics of Jackfruit Chips in Tambang District - Ningsih, Arum Rovarti; Novianti, Nadya; Nasution, Addiena Syahvina; Masyitah, Masyitah; Ihsan, Fikratul; Endyra, Fadlila (PUI BiGME Universitas Jambi, 2026)
Jackfruit chips are a promising product choice because, in addition to their relatively easy production process and low raw material costs, they can also be sold at affordable prices. However, the biggest challenge for MSMEs is maintaining consistent product quality to meet consumer expectations and maintaining competitiveness in an increasingly competitive market. This research will be conducted in Tambang District, Kampar Regency, Riau Province. Samples will be taken from three jackfruit chip MSMEs in Tambang Subdistrict, Kampar Regency, namely Usaha Baru Ibu, Sinar Hidayah, and Restu. Sample testing will be carried out at the Riau University Agricultural Product Analysis Laboratory, the Andalas University Instrumentation Laboratory, and the Pekanbaru Goods Quality Testing and Certification Technical Implementation Unit. The observation of jackfruit chip quality based on SNI 01-4269-1996 was conducted at Sinar Hidayah SME, Usaha Baru Ibu SME, and Restu SME. The parameters observed were moisture content, ash content, fat content, texture of jackfruit chips, and descriptive test. The results of identifying the processing and quality characteristics of better jackfruit chips were obtained by Restu MSME with a frying process at a temperature of 97˚C, vacuum pressure of 75 cmHg for 3 hours, resulting in a moisture content of 5.32%, ash content of 2.13%, fat content of 11.14%, hardness test of 114.70 N/cm2, and a descriptive test of 4.65.